The Effect of Debt and Working Capital on Profitability (Case Study on Retail Trade Sub-Sector Companies Listed on The Indonesian Stock Exchange Period 2020-2022) - Sayyid Abdul Ghany; Seflidiana Roza; Esi Sriyanti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of debt and working capital on the profitability of retail trade sub-sector companies listed on the Indonesian stock exchange for the 2020-2022 period. The financial ratios studied are Debt and Working Capital. The population in this research is retail trading sub-sector companies on the Indonesian Stock Exchange for the 2020-2022 period. The sample consisted of 24 companies that published complete financial reports for 3 years (2020-2022) using the purposive sampling method, namely a sample selection technique using certain criteria that the researcher had determined for the object under study. Data collection was carried out using documentation methods, literature study and accessing the web and related sites. Data analysis was carried out using multiple linear regression analysis. The research results show that the debt variable has a partially significant effect on profitability. Meanwhile, the working capital variable has a partially significant effect on profitability. Simultaneously, it was found that debt and working capital jointly influence profitability with R2 0.171 (17.1%). Keywords: Debt, Working Capital, Profitability